2018
DOI: 10.1136/bmjopen-2018-021983
|View full text |Cite
|
Sign up to set email alerts
|

Which type of tobacco product warning imagery is more effective and sustainable over time? A longitudinal assessment of smokers in Canada, Australia and Mexico

Abstract: ObjectiveThis study examined smokers’ responses to pictorial health warnings (PHWs) with different types of imagery under natural exposure conditions.MethodsAdult smokers from online panels in Canada (n=2357), Australia (n=1671) and Mexico (n=2537) were surveyed every 4 months from 2012 to 2013. Participants were shown PHWs on packs in their respective countries and asked about: (1) noticing PHWs; (2) negative affects towards PHWs; (3) believability of PHWs; (4) PHW-stimulated discussions; and (5) quit motivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…Our results have important implications for warning design, and supports previous research which found that responses differed by warning content [1,54]. Visual attention was greater for long‐ versus short‐term warnings (study 1) but did not differ by warning framing (study 2) or severity (study 3).…”
Section: Discussionsupporting
confidence: 88%
“…Our results have important implications for warning design, and supports previous research which found that responses differed by warning content [1,54]. Visual attention was greater for long‐ versus short‐term warnings (study 1) but did not differ by warning framing (study 2) or severity (study 3).…”
Section: Discussionsupporting
confidence: 88%
“…While this innovation may have added value to smoking that helped to offset the cost of the last tax increase in 2011, further periodic increases in taxes may be necessary, especially given the evidence for the effectiveness of earlier tax increases. Also, the relatively small health warning on the front of the pack (30%) should be increased to align with FCTC guidelines 28 43 44…”
Section: Discussionmentioning
confidence: 99%
“…In the second step, the team reviewed existing HWLs for cigarettes (www.tobaccolabels.org), including those initially proposed by the US Food and Drug Administration for cigarettes39 to identify the most effective HWLs (images of bodily harm, people suffering the consequences of smoking)40–43 that could be adapted for WP, as well as HWLs that had already been developed and tested for WP 12. As suggested by ‘semantic priming’, where the editorial context acts as a prime and activates viewers’ related knowledge and memory,44 for each HWL, the text content was adapted based on WP-specific evidence, consistent with theme, and was designed to convey a clear, simple and direct message.…”
Section: Methodsmentioning
confidence: 99%